Detection of De Novo PAX2 Variants and Phenotypes in Chinese Population: A Single-Center Study - Xiong, Hua-Ying; Shi, Yong-Qi; Zhong, Cheng; Yang, Qin; Zhang, Gaofu; Yang, Haiping; Wu, Daoqi; Chen, Yaxi; Li, Qiu; Wang, Mo (Frontiers in Genetics, 2022)
Abstract Background: PAX2 is a nuclear transcription factor gene that is highly conserved among species. Variants within PAX2 could result in optic nerve colobomas and kidney hypoplasia. However, little clinical and genetic information is currently available about PAX2 variants in Chinese children. Objective: This study aimed to further understand the clinical manifestations and genetic characteristics of PAX2 variants in the Chinese population. Methods: In this single-center retrospective study, we analyzed the clinical data of ten children identified as carriers of PAX2 variants by gene sequencing. All the variants found in this study were analyzed using in silico prediction and American College of Medical Genetics and Genomics (ACMG) standards and guidelines. Results: The mean age for developing the first symptom in 10 unrelated children was 7.2 years old. Proteinuria and bilateral kidney dysplasia were found in every patient. Two children underwent kidney histological examination, one child showed high-intensity C1q deposition in the kidney, and the other child showed focal segmental glomerular sclerosis (FSGS). Three children had PAX2-related ocular abnormalities, including nystagmus, retinal exudation, amblyopia, microphthalmia, microcornea, and total blindness. In addition, one patient had the comorbidity of oculocutaneous albinism (OCA). Eight different PAX2 variants were found in ten patients, three of which were reported for the first time. Conclusion: We reported some patients with unique manifestations and comorbidities, and we reported three variants that have not been previously identified. The PAX2 gene is prone to spontaneous variants, and the outcome of patients is unfavorable. Because of the lack of specific therapy, genetic testing should be recommended for individuals with obvious evidence of kidney dysplasia and eye abnormalities, and kidney protective treatment should be initiated early.